2015
DOI: 10.1038/nature14623
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of a polypeptide processing and secretion transporter

Abstract: Bacteria secrete peptides and proteins to communicate, to poison competitors, and to manipulate host cells. Among the various protein-translocation machineries, the peptidase-containing ATP-binding cassette transporters (PCATs) are appealingly simple. Each PCAT contains two peptidase domains that cleave the secretion signal from the substrate, two transmembrane domains that form a translocation pathway, and two nucleotide-binding domains that hydrolyse ATP. In Gram-positive bacteria, PCATs function both as mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
176
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(192 citation statements)
references
References 53 publications
15
176
1
Order By: Relevance
“…The crystal structures of exporters display varying degrees of NBD disengagement in the absence of nucleotides (Ward et al , 2007; Lin et al , 2015; Perez et al , 2015; Bountra et al , 2017). These data were questioned as a detergent artifact mistaken for dynamic NBDs.…”
Section: Discussion and Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…The crystal structures of exporters display varying degrees of NBD disengagement in the absence of nucleotides (Ward et al , 2007; Lin et al , 2015; Perez et al , 2015; Bountra et al , 2017). These data were questioned as a detergent artifact mistaken for dynamic NBDs.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…DEER data of ABC transporters in liposomes and bicelles show broad lines for apo NBDs (Dong et al , 2005; Borbat et al , 2007; Zou et al , 2009; Bountra et al , 2017), further suggesting that in the absence of nucleotides the NBDs can have different degrees of disengagement. Upon nucleotide binding, the NBDs dimerize and display nearly identical distances across different transporters (Ward et al , 2007; Lin et al , 2015; Perez et al , 2015; Bountra et al , 2017). Our smFRET data in detergent and liposomes revealed that the NBDs of McjD adopt very similar disengagement with E* values of 0.3 and larger E* values of 0.5 upon nucleotide binding.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…The presence of the occluded conformations along the transport cycle probably acts as (i) a shielding mechanism for preventing peptide re‐uptake by McjD and (ii) a mechanism to prime McjD for MccJ25 binding, during its biosynthesis, without building up toxic levels of the peptide (Choudhury et al , 2014). The structures of the peptidase‐containing ATP‐binding cassette transporter (PCAT) PCAT1 from Clostridium thermocellum (Lin et al , 2015) and the lipid‐linked oligosaccharide flippase PglK from Campylobacter jejuni (Perez et al , 2015) have also been determined in a nucleotide‐bound outward‐occluded conformation and without domain intertwining similar to McjD. Therefore, the mechanism we propose for McjD is probably relevant to other ABC transporters that are dedicated to specific substrate export, whose cavity is “immediately shielded” upon substrate release.…”
Section: Discussionmentioning
confidence: 99%
“…In ABC transporters, replacing the Glu of the Walker B motif with a Gln has been frequently utilized to eliminate ATPase activity, while preserving the ability to bind ATP (Lee et al, 2014;Lin et al, 2015). Upon co-expression of the corresponding Dd-PrtD-E492Q mutant with PrtE and PrtF, we observe no secretion into the media even after 18 hr of PrtG induction, (Right panel, Fig.…”
Section: Substrate Secretion Is Dependent On Atp Hydrolysismentioning
confidence: 95%
“…The large size of T1SS substrates suggest that the transporter operates in a distinct mechanism from peptide ABC transporters such as microcin exporters and the human antigen transporters, TAP1/2 (Choudhury et al, 2014;Grossmann et al, 2014;Eggensperger and Tampe, 2015;Lin et al, 2015). These transporters appear to operate by the 'alternating access' mechanism whereby the peptide binds from the cytoplasmic side (Rees et al, 2009;Beek et al, 2014;Locher, 2016).…”
Section: Octyl Udp-6-thio-α-d-galactopyranose Disulfide (7)mentioning
confidence: 99%